1972
DOI: 10.2134/agronj1972.00021962006400020028x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on the Leaf Temperatures of Two Soybean Varieties Grown under Controlled Irrigation1

Abstract: Remote sensing techniques have been suggested as a possible tool to the agricultural research worker. In addition, plant leaf temperatures (a quantity capable of being measured by remote sensors) give an indication of the plant's response to the environment. For these reasons, an experiment was conducted in the field to investigate the relations between plant leaf temperatures and soil moisture stress and various environmental parameters. Leaf temperatures (TL) of two soybean [Glycine max (L.) Merr.] varieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This method is based on the fact that the difference between canopy and air temperatures (T c −T a ) increases when crops are under water stress, in response to decreased evapotranspiration, which serves as a cooling mechanism for the crop (Wolpert 1962;Gates 1964;Linacre 1964;Conaway and van Bavel 1967;Fuchs and Tanner 1966;Carlson et al 1972). It is known that (T c −T a ) is linearly related to air vapor pressure deficit (VPD) .…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on the fact that the difference between canopy and air temperatures (T c −T a ) increases when crops are under water stress, in response to decreased evapotranspiration, which serves as a cooling mechanism for the crop (Wolpert 1962;Gates 1964;Linacre 1964;Conaway and van Bavel 1967;Fuchs and Tanner 1966;Carlson et al 1972). It is known that (T c −T a ) is linearly related to air vapor pressure deficit (VPD) .…”
Section: Introductionmentioning
confidence: 99%
“…Aston and van Bavel (1972) proposed the canopy temperature variability method but did not provide actual values which would signal the onset of stress. They and Carlson et al (1972) showed that (T c -T a ) values are negatively correlated with relative leaf water content. They also stated that this value was valid only when the canopy cover was nearly complete.…”
Section: Crop Stress Measurements By Infrared Thermometrymentioning
confidence: 97%
“…Tanner (1963) suggested that the temperature difference between stressed and unstressed plant leaves gave a quantitative indication of differences in transpiration potential. Leaf temperature was associated with leaf water content (Carlson et al 1972) and the gradient of temperature between leaf surface and air boundary (DT C-A ) increased following irrigation (Ehrler 1973). Gardner et al (1981) reported that canopy temperature closely followed ambient air temperature, and the profile of leaf and air temperature of stressed and unstressed canopy were similar.…”
Section: Introductionmentioning
confidence: 99%